Body-image and obesity in adolescence: a comparative study of social-demographic, psychological, and behavioral aspects - Lopes de Sousa, Pedro Miguel (The Spanish Journal of Psychology, 2008)
In current society, body and beauty’s cult emerge as one of the main factors of adolescence. That leads adolescents to be dissatisfied with their own appearance, to psychological maladjustment, and nutritional disorders. This quantitative, exploratory, and cross-sectional research evaluates how adolescents perceive their weight and the prevalence of obesity in a sample of adolescents from the district of Viseu (Portugal). It also attempted to compare the relation of body-image and obesity with sociodemographic (school, sex, age, socioeconomic status, family functioning), psychological (self-concept, depression, school success) and behavioral aspects (physical inactivity). After data analyses, it was verified that the prevalence of obesity was 8.8% but 12.7% considered themselves obese. These adolescents had higher physical inactivity, poorer family functioning, a lower self-concept, and a higher depression index. The really obese adolescents were older and had poorer academic results. Obesity was higher in boys, but girls perceived themselves more as being obese. In conclusion, it is essential to evaluate weight perception in addition to body mass index (BMI), because the main problem could be related not only to being obese, but also to the perception of having a higher than ideal weight.